Facilitating and supporting the elite athlete-to-coach transition: Lessons learned from Norwegian coaches and federations - Chroni, S. A.; Dieffenbach, K, (Journal of Sport Psychology in Action, 2021)
Elite athletic career termination is inevitable in high performance sport. Whether due to interest, injury, age or combination of factors, athletes will undergo a shift in their professional and personal identity. While retirement out of sport has been scrutinized to both understand and support athletes, we have not thought through what the athlete-to-coach, within-sport retirement, signifies for the person undergoing it and for our applied practice and lack the approach(es) for supporting it. Based on recent research advances, we build on a range of resources to be developed in supporting athletes during the transition and in the coaching profession.